2012
DOI: 10.1523/jneurosci.1088-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal Connectivity Underlies Individual Differences in the Balance between Habitual and Goal-Directed Action Control

Abstract: Why are some individuals more susceptible to the formation of inflexible habits than others? In the present study, we used diffusion tensor imaging to demonstrate that brain connectivity predicts individual differences in relative goal-directed and habitual behavioral control in humans. Specifically, vulnerability to habitual "slips of action" toward no-longer-rewarding outcomes was predicted by estimated white matter tract strength in the premotor cortex seeded from the posterior putamen (as well as by gray m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
261
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(285 citation statements)
references
References 49 publications
24
261
0
Order By: Relevance
“…reaching the target regions) of the 25,000 samples sent out per each effective voxels (i.e. those voxels that were located in the white matter) in the seed and a target ROI (Croxson et al, 2005;de Wit et al, 2012;Gschwind et al, 2012). The number of successful samples was then normalized by the total number of all successful samples across all investigated seed and target regions for each subject in each hemisphere.…”
Section: Image Processing and Data Analysismentioning
confidence: 99%
“…reaching the target regions) of the 25,000 samples sent out per each effective voxels (i.e. those voxels that were located in the white matter) in the seed and a target ROI (Croxson et al, 2005;de Wit et al, 2012;Gschwind et al, 2012). The number of successful samples was then normalized by the total number of all successful samples across all investigated seed and target regions for each subject in each hemisphere.…”
Section: Image Processing and Data Analysismentioning
confidence: 99%
“…Although P as a temperament trait was paid less attention by researchers compared to other three temperaments, similar behavioral constructs such as "perseveration" (de Ruiter et al, 2009;Serpell et al, 2009) and "habit formation"/goal-directed behaviors (de Wit et al, , 2012 in humans and animals have been extensively discussed in the fields of neuropsychology, neurology, and psychiatry . Results of these studies also showed that the ventromedial prefrontal cortex played an important role in "perseveration" …”
Section: Persistencementioning
confidence: 99%
“…Some neuroimaging studies have demonstrated that one of the most salient aspects of moral development at the neural level during early-childhood through early-adolescence is that brain regions associated with the motivational and reward system (e.g., amygdala, nucleus accumbens, orbitofrontal cortex, ventral striatum), which engages in the habituation and internalization of rules (Wilson and Rolls 2005;Blair 2007), develop earlier than regions associated with sophisticated reasoning (Galvan et al 2006;Hare et al 2008;Decety et al 2012). This aspect would also be supported by neuroimaging studies demonstrating that habituation actually influences the neural mechanism of affection and motivation (Tricomi et al 2009;Lingawi and Balleine 2012;de Wit et al 2012). Then, in regions correlated with reasoning based on prudence, self-control, and sophisticated self-reflective processes (e.g., lateral prefrontal cortex, posterior cingulate cortex) Buckner et al 2008;Immordino-Yang et al 2012), that correspond to the concept of phronesis in Aristotelian philosophy, the activity becomes salient beyond adolescence Wright et al 2008;Harenski et al 2012).…”
Section: Development Of Moral Virtue and Developmental Neurosciencementioning
confidence: 82%
“…Second, even for the cultivation of reasoning, which is more sophisticated than the case of habituation, interventions, such as board games (Lee et al 2010), reasoning exercises (Mackey et al 2012), working memory training (Olesen et al 2004;Takeuchi et al 2010), and meditation programs (Lazar et al 2005), promoted significant structural changes in brain regions associated with cognition and reasoning. These results would support the idea that Aristotelian ways for moral education-i.e., habituation and phronesis cultivation-actually influences the brain structure according to the idea of neuroplasticity (LeDoux 2002) and previous neuroscientific studies demonstrating the neural-level effect of habituation and learning (Tricomi et al 2009;Lingawi and Balleine 2012;de Wit et al 2012). …”
Section: Development Of Moral Virtue and Developmental Neurosciencementioning
confidence: 94%